HISTOLOGIC FEATURES AND GRANULOCYTE WHITE BLOOD CELL COUNTS OF YOUNG AND ADULT SUMBAWA HORSES REARED UNDER THE LAR SYSTEM - Angelica Ramadya Putri Candrianisa; Ni Ketut Suwiti; Tjokorda Sari Nindhia; Ni Luh Eka Setiasih; Anak Agung Sagung Kendran; I Ketut Suatha (Buletin Veteriner Udayana, 2024)
Leukocytes, are a crucial component of the immune system, protecting the body from infections such as bacteria, viruses, fungi, or parasites. This study aims to determine the histological structure of granulocyte white blood cells—basophils, eosinophils, and neutrophils—in young and adult Sumbawa horses. Blood samples were taken from 10 young and 10 adult Sumbawa horses, and histology preparations were made using eosin and methylene blue staining (MDT IndoReagen®). The histological examination and cell counts were conducted using an Olympus CX33 microscope, and data were analyzed with the T-test. The results showed that the histological structure of granulocyte leukocyte in both young and adult Sumbawa horses consisted of round cells with visible cytoplasm and nucleus. Neutrophils have 3-5 lobes with highly variable nucleus shapes and pale pink cytoplasm. The mean number of neutrophils in young Sumbawa horses was 34.20 ± 5.613%, while in adults it was 54.00 ± 6.324%. Eosinophils have a nucleus with two segmented lobes and very clear purplish-red granules in the cytoplasm. The number of eosinophils in young Sumbawa horses was 10.90 ± 2.726%, higher than in adults at 4.10 ± 1.595%. Basophils have very clear purplish-blue granules, with one nucleus filling almost the entire cytoplasm. The mean number of basophils in young Sumbawa horses was 0.20 ± 0.421%, and in adults, it was 0.10 ± 0.316%. In conclusion, the histological images of granulocyte leukocyte in Sumbawa horses show very clear granules, with the number of neutrophils young horses being lower than in adults and eosinophils being higher in young horses than in adults (P<0.05). However, there was no significant difference in the number of basophils (P>0.05). Further research is needed to compare the histology and agranulocyte white blood cell counts in Sumbawa horses to obtain more comprehensive information.